PELATIHAN PENGGUNAAN TEKNOLOGI DIGITAL DALAM PEMBELAJARAN BAHASA INGGRIS BAGI GURU DI MI MUHAMMADIYAH KAMULAN - Moh. Huda; Nugrananda Janattaka (Politeknik Negeri Sriwijaya, 2023)
English language learning plays a crucial role in preparing the younger generation to face global challenges. English is widely used in global communication, including in the fields of technology and business. The use of digital technology in English language learning can enhance the quality of education and the accessibility of educational materials. Specialized training for teachers is essential to prepare students for global challenges. MI Muhammadiyah Kamulan, a primary school in a rural area, faces challenges in utilizing digital technology for English language learning. Specific training is required for teachers to effectively teach English and create an engaging learning environment. This training also has a positive impact on students by improving access to quality learning resources. This report will document the training process and provide insights into the importance of digital technology training in enhancing English language learning at the primary school level.